Healthcare professionals' perceptions of pain in infants at risk for neurological impairment - Camfield Carol S; Beyene Joseph; Stevens Bonnie; McGrath Patrick J; Breau Lynn M; Finley G Allen; Franck Linda; Howlett Alexandra; O'Brien Karel; Ohlsson Arne (BMC, 2004)
Abstract Background To determine whether healthcare professionals perceive the pain of infants differently due to their understanding of that infant's level of risk for neurological impairment. Method Neonatal Intensive Care Units (NICU's) at two tertiary pediatric centers. Ninety-five healthcare professionals who practice in the NICU (50 nurses, 19 physicians, 17 respiratory therapists, 9 other) participated. They rated the pain (0-10 scale and 0-6 Faces Pain Scale), distress (0-10), effectiveness of cuddling to relieve pain (0-10) and time to calm without intervention (seconds) for nine video clips of neonates receiving a heel stick. Prior to each rating, they were provided with descriptions that suggested the infant had mild, moderate or severe risk for neurological impairment. Ratings were examined as a function of the level of risk described. Results Professionals' ratings of pain, distress, and time to calm did not vary significantly with level of risk, but ratings of the effectiveness of cuddling were significantly lower as risk increased [F (2,93) = 4.4, p = .02]. No differences in ratings were found due to participants' age, gender or site of study. Physicians' ratings were significantly lower than nurses' across ratings. Conclusion Professionals provided with visual information regarding an infants' pain during a procedure did not display the belief that infants' level of risk for neurological impairment affected their pain experience. Professionals' estimates of the effectiveness of a nonpharmacological intervention did differ due to level of risk.